2009
DOI: 10.2903/j.efsa.2009.1330
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the re-evaluation of Sunset Yellow FCF (E 110) as a food additive

Abstract: The Panel on Food Additives and Nutrient Sources added to Food provides a scientific opinion re-evaluating the safety of Sunset Yellow FCF (E 110). Sunset Yellow FCF has been previously evaluated by JECFA and the SCF. Both committees established an Acceptable Daily Intake (ADI) of 0-2.5 mg/kg bw/day. The Panel was not provided with a newly submitted dossier and based its evaluation on previous evaluations, additional literature that became available since then and the data available following a public call for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 53 publications
1
15
0
2
Order By: Relevance
“…Furthermore, the test material in the Mathur studies was not characterised and was bought on the local market. A 28-day study was considered sufficient to study the effects on the testis, as no effects on fertility in a reproductive toxicity study in rats, and no relevant histopathological changes were reported in long-term studies in mice and rats (EFSA ANS Panel, 2009). The Panel noted that a 28-day study would also be sufficient for considering the effects reported on the blood lipid profile.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the test material in the Mathur studies was not characterised and was bought on the local market. A 28-day study was considered sufficient to study the effects on the testis, as no effects on fertility in a reproductive toxicity study in rats, and no relevant histopathological changes were reported in long-term studies in mice and rats (EFSA ANS Panel, 2009). The Panel noted that a 28-day study would also be sufficient for considering the effects reported on the blood lipid profile.…”
Section: Discussionmentioning
confidence: 99%
“…The European Food Safety Authority (EFSA) has re-evaluated the safety of Sunset Yellow FCF (E 110) as a food additive in 2009 (EFSA ANS Panel, 2009).…”
Section: Background As Provided By the European Commissionmentioning
confidence: 99%
See 3 more Smart Citations